Pengaruh Kepemimpinan, Kompetensi Kerja, Keterlibatan Kerja terhadap Kepuasan Kerja pada Dinas Perhutani Semarang - Alvidya Laksana Putri; Tristiana Rijanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to analyze the influence of leadership, competence and work involvement on job satisfaction. This research was conducted at Perum Perhutani Central Java Division. The sampling technique uses a purposive sampling method with the criteria of being at least 21 years old, having a minimum of 3 years of work with a minimum of SMA/SMK education and being a permanent employee of Perum Perhutani, Central Java Division. The number of samples in this study was 70 respondents. The data analyzed is primary data collected using a questionnaire. The results of data processing are in the form of respondent descriptions, variable descriptions, validity test results, reliability tests, F test results, R² coefficient of determination test results and hypothesis test results. The research results show that leadership has a positive and significant effect on job satisfaction, competence has a positive and significant effect on job satisfaction and work involvement has no effect on job satisfaction.